PENGUATAN IDENTITAS LOKAL DAN OPTIMALISASI POTENSI DESA OLILIT MELALUI PENDEKATAN SOSIO-BUDAYA, EKONOMI, DAN POLITIK KABUPATEN KEPULAUAN TANIMBAR - Muhtar, Muhtar; Desviona, Nayla; Rukoyah, Rukoyah (Jurnal Abdimas Bina Bangsa, 2025)
This service was designed with the aim of strengthening local identity, involving all stakeholders, and optimizing village potential into strategic steps to overcome existing problems. Through a participatory approach that involves all elements of the community. Community service in Olilit Village succeeded in identifying problems and utilizing local potential which includes socio-cultural, economic, and political governance aspects of the village. Through training and mentoring, the community's skills in product diversification and community-based tourism management have been improved, although challenges in marketing access and land conflicts require further solutions. In village governance, the implementation of financial management transparency has increased community trust in the village government, although political fragmentation is an obstacle. Political education and the establishment of regular deliberation forums are recommended to realize inclusive and equitable governance. Overall, strengthening local identity, community empowerment, and community-based potential management are effective strategies to create harmonious village development between tradition and modernity. This model is expected to be an inspiration for other villages in Eastern Indonesia.